Answer :
Answer:
It is necessary to sum 8 units
Step-by-step explanation:
you have the following polynomial:
[tex]f(x)=x^2-6x+1[/tex] (1)
To complete the square you take into account the following general notable product:
[tex](a-b)^2=a^2-2ab+b^2[/tex]
Next, you take into account the coefficient of the second term in (1)
-6x = -2ab
a = x
-6a = -2ab
b = 6/2 = 3
Then, the third term must be:
b^2 = 3^2 = 9
But you have +1. Hence, you must sum 8, and also rest 8 in (1):
[tex]f(x)=x^2-6x+(1+8)-8\\\\f(x)=(x^2-6x+9)-8\\\\f(x)=(x-3)^2-8[/tex]